Fascism in Israel. The Funding of Fascist and Neo-Nazi Movements: 1970-1990 - Shimshon Bichler; Jonathan Nitzan; Robin Rowley (The Bichler & Nitzan Archives, 1989)
In 1989, we applied for a Harry Frank Guggenheim Foundation grant to investigate the funding of fascist and Neo-Nazi movements in Israel. The Foundation did not find the topic important enough, and the application was ceremonially rejected. Here is what we wanted to do. RESEARCH PLAN. The emergence of ultra right-wing elements in Israeli society has drawn considerable attention from the popular media both in Israel and elsewhere. Academic studies on the subject have often considered this rise of fascist and neo-Nazi organizations as a marginal development rather than as part of a broader political transformation. We argue, to the contrary, that the rise of ultra- right movements reflects important changes in Israel and was both stimulated by actions of the Israeli government and supported by business organizations and affluent individuals (both in Israel and abroad). Our study focuses on the potential link between the fascist and neo-Nazi organizations and the mainstream of Israel's political and economic spheres. In particular, we seek to map the flow of funding to such organizations from government, business and foreign sources. Three avenues of research will be followed. (i) Analysis of government budgets, records of business transactions and registration of donations. (ii) Interviews with key individuals in the political, military and business elites, others who were instrumental to financial support for extreme right-wing movements and central figures in these movements themselves, (iii) Close examination of existing publications, particularly newspapers and magazines, that reported on Israeli fascism since 1970. Results will be organized in an input -output format between source and destination for funds. A dynamic temporal comparison between alternative periods could provide important insight into the evolution of extreme right-wing movements and their relations with the central establishment of Israeli society. RELEVANCE TO HUMAN DOMINANCE, AGGRESSION AND VIOLENCE. Fascists and neo-Nazi movements have been involved in numerous violent and illegal activities against Arabs in the Occupied Territories as well as against political opponents in Israel. Their ideologies advocate the creation of a totalitarian society, an authoritarian economy run by a military bureaucracy and an official apartheid against the Palestinian population. In matters of foreign policy they call for a permanent state of war against the Arab neighbours and an aggressive expansionary drive to create a "big Israel". This vision of dominance may have grave consequences for aggression and violence in Israel and the Middle East. Such sombre prospects are enhanced by the extent to which ultra right-wing movements are supported by Israel's mainstream establishment.
Keywords: P16; G; 330; fascism; finance; Israel; Neo-Nazism